Study of the results of 155 liver resections - Torterolo, Edgardo; Silva, Celso; Cidade, Luis; Czarnevicz, Daniel; Leites, Alejandro; Vergara, Mirtha; Aizen, Bernardo; Ferreira, Carlos; Bergalli, Luis; Fernández, Miguel; Kaitazzof, Pedro; Perdomo, Susana; et al. (Cirugía del Uruguay, 1994)
The authors analyse a series of 155 patients that underwent hepatic resections between 1972 and 1991. The diagnostica/ elements of the different etiologies, surgica/ indications and results as regards complications and mortality are considered. The authors a/so make considerations on different changes in criteria as regards resectability and mortality causes, emphasizing hepatic failure as the main one. They a/so point out the need to preserve hepatic parenchyma provided that oncological criteria are kept to.